The Concept of Stimmung and the Creation of Objective Moods in Movies: “Kerr” (2021) Movie Review - Selcuk Ulutas; Murat Aytaş (Галактика медиа: журнал медиа исследований)
Every movie is a mental design objectifying intentional images. Movies aim to influence the audience at certain levels, intellectually and effectively. The stylistic order enables films to create non-subjective effects. This study expands the boundaries of affect and focuses on the relationship between episodic emotions and long-lasting moods in cinema. It also supports the idea that mood is an affect designed in motion pictures. Moods are subjective in everyday life. The main suggestion of the study is that it is possible to produce moods objectively in movies. This issue regarding moods finds a vast place in philosophy within the framework of Stimmung. Stimmung expresses an objective state of mind that is not subjective and spreads to large masses. At this point, the study’s primary purpose is to show that it is possible to create an objective mood designed in cinema films and the effectiveness of these moods in determining the affective and intellectual levels of the movie. We used the literature review method. In addition, director Tayfun Pirselimoğlu’s film “Kerr” (2021), determined by the purposeful sampling method, was examined with the phenomenological analysis method. As a result of the analysis, it emphasized that the director produced anxiety as a Stimmung in the sample film. The anxious mood directly affects the movie’s intellectual and affective design. The tense mood directly affects the movie's intellectual and affective design.